Peripheral ameloblastic carcinoma of the mandible: Report of two cases with different types. Issue 3 (23rd February 2020) - Sumita, Yoshinori; I, Takashi; Kawasaki, Takako; Hara, Masahito; Fujita, Shuichi; Asahina, Izumi
Abstract: Peripheral ameloblastic carcinoma is a rare odontogenic tumor that is characterized by malignant cytological features in combination with histological features of ameloblastoma. In this report, two cases of peripheral ameloblastic carcinoma of different types arising at the mandibular gingiva are presented. Both patients had marginal resection after incisional biopsy and were diagnosed as ameloblastic carcinoma according to WHO classification in 2017. However, two cases had distinct pathological features. First case had no finding suspicious of malignant transformation from benign ameloblastoma (primary type with 2005 WHO classification), while the other case showed benign ameloblastoma with malignant changes within the gingiva (secondary type with 2005 WHO classification).